Peran Komunikasi Organisasi Pemerintahan Desa dalam Peningkatan Kinerja Pemerintahan Desa di Kecamatan Cot Girek, Aceh Utara - Mulyadi Rasimun; Dwi Sadono; Cahyono Tri Wibowo (Jurnal Komunikasi Pembangunan, 2017)
Implementation of village legislation needs the role of organizational communication, especially for organization of village administration in order to realize improved performance and rural development. Organization could run streamlined and successfully with a good communication. The objectives were (1) analyzing the role of organizational communication in the implementation of village legislation to villagers, and (2) finding out the performance improvement of village administration in rural development which is based on the village legislation. The study result showed the role of organizational communication of village administration that related with perception of village officials to village legislation which; the individual characteristics of the village administration officials were: age, gender, education level, and employment, while they werenot related: income level. Village admnistration characteristic that related to perception of village officials to village legislation were: the leadership role, organizational structure and organizational culture. Organizational communication of village administration that related with perception of village officials to village legislation were: communicator, request and media. Government's role as the pioneer of rural development was fully able to in addressing development issues in the village such as the planning of rural development programs, socialization activities in Meunasah and was attended by most villagers, in the village meetings activities were not only socializing by one direction, but public was also given their opportunity to speak as well as their opinion.